The development of educational game-based learning media in natural science subject for elementary school students - Riri Okra (Universitas Negeri Yogyakarta, 2023)
This research is based on the lack of innovative learning media that is easily accessible and suitable for the characteristics of students. This research aims to produce a learning media in the form of science learning educational games aimed at fifth-grade elementary school students. This educational game was developed using Construct2. This type of research is research and development (RnD) with the 4D development model (Define, Design, Develop and Disseminate). This educational game validation was obtained from media experts consisting of lecturers, practitioners, and teachers whose fields correspond to the media being developed. The questionnaire distributed to media experts obtained an average value of 0.97 which was categorized as valid. This educational game was also tested on users consisting of 21 fifth grade elementary school students, and obtained an average score of 94.15 in the very good category, this indicates that the science learning educational game for elementary school children is also very suitable for grade students. V elementary school which is evident from the assessment of grade V elementary school students who stated that this media was very good.